2018
DOI: 10.22153/kej.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Cutting Parameters on Temperature Distribution and Tool Life During Turning Stainless Steel 316L

Abstract: This paper is focused on studying the effect of cutting parameters (spindle speed, feed and depth of cut) on the response (temperature and tool life) during turning process. The inserts used in this study are carbide inserts coated with TiAlN (Titanum, Aluminium and Nitride) for machining a shaft of stainless steel 316L. Finite difference method was used to find the temperature distribution. The experimental results were done using infrared camera while the simulation process was performed using Matlab softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The impact of the machining conditions on flank wear and cutting temperature during turning of the AISI 316L has been studied by Akbar et al [4]. The authors found that with high Vc, f, and depth of cuts, the cross section of ships increase which led to increase the maximum temperature and tool wear, which cause a decrease in the tool life.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the machining conditions on flank wear and cutting temperature during turning of the AISI 316L has been studied by Akbar et al [4]. The authors found that with high Vc, f, and depth of cuts, the cross section of ships increase which led to increase the maximum temperature and tool wear, which cause a decrease in the tool life.…”
Section: Introductionmentioning
confidence: 99%